The Pan-African High-K I-Type Granites From Batié Complex, West Cameroon: Age, Origin, and Tectonic Implications - Kwékam, Maurice; Talla, Victor; Fozing, Eric Martial; Tcheumenak Kouémo, Jules; Dunkl, István; Njonfang, Eammanuel (Frontiers in Earth Science, 2020)
The Batié granitic massif in western Cameroon is NE–SW elongated, follows the regional foliation, and is parallel to the Kekem–Fotouni shear zone, which is the southwestern extension of the Tcholliré–Banyo Fault (TBF). This massif comprises two petrographic units: biotite granite and amphibole granite. Major, trace, REE, Sr–Nd isotopic, and new U–Pb data are used to constrain their nature and origin. The results indicate that they are high-K alkali-calcic with shoshonite affinity. The amphibole granite is metaluminous, whereas biotite granite is weakly peraluminous. Both granites are high-temperature I-type granites and crystallized under oxidizing conditions. Initial (87Sr/86Sr)620 Ma ratios (0.7062–0.7080) and εNd620 Ma (−12.6 to −8.9) indicate that the parental magmas were produced by partial melting of thick Paleoproterozoic crust and were mixed with felsic magma from the upper continental crust. Their Nd TDM typically varies from 1.68 to 1.96 Ga. The massif was mostly emplaced between 630 and 547 Ma during the transitional period between the crustal thickening (630–610 Ma) and the development of the shear zones, which began with sinistral movements (610–580 Ma) and continued with dextral movements (585–540 Ma). Plutonism continued during the dextral movements. The Batié granite is geochemically and isotopically similar to other post-collisional pan-African granitic massifs located along the TBF.